Ամենայն Հայոց Կաթողիկոս Գեւորգ Ե. Սուրէնեանցի ազգանպաստ գործունէութիւնը - Մելիքեան, Արեւիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
The article aims to present the activities of Catholicos Gevorg V Surenyants for the benefit of the Armenian people. It is based mainly on archival documents, memoirs and impressions of contemporaries, the original encyclicals of Gevorg V Surenyants stored in the “Document” storage of the Museum of Armenian Ethnography. The purpose of the article is to restore the historical memory of the Armenian people by referring to the events of the first half of the XX century, in which the Supreme Patriarch played a significant role. Gevorg V Surenyants won the love and sympathy of the Armenian people by his deeds. The work he has done was important not only for the Armenian Apostolic Church, but for the history of the Armenian people as well. Gevorg V Surenyants was destined to see the genocide of his people, the heroic battles of May 1918, the proclamation and fall of the First Republic of Armenia and its sovietization. He was the Catholicos during the Soviet era, too, when the Church was severely persecuted. His appeal to Armenians all over the world, in which he called for supporting Soviet Armenia and improving its economic condition, was of great significance. Today, when the Armenian people are going through difficult times — we have lost Artsakh and our statehood is under threat, it is more relevant to turn to this patriotic religious figure and raise the spirit of the people through his image with the intent on inspiring hope for the future. В статье представлена деятельность католикоса Геворга Суренянца на благо армянского народа. Она преимущественно основана на архивных документах, воспоминаниях и впечатлениях современников, оригинальных кондаках Геворга V Суренянца, хранящихся в фонде «Документ» Музея этнографии армян. Цель статьи — восстановить историческую память армянского народа, обратившись к событиям первой половины XX века, в которых Верховный Патриарх сыграл значительную роль. Своими делами Геворг Суренянц завоевал любовь и сочувствие армянского народа. Его деятельность важна не только для Апостольской Церкви, но и для истории армянского народа в целом. Геворгу V Суренянцу было суждено уви- деть геноцид своего народа, героические майские сражения 1918 года, провозглашение и падение Первой республики Армения, советизацию Армении. Он также был Католикосом в советское время, когда церковь подвергалась серьезным преследованиям. Имело огромное значение его обращение к армянам всего мира, в котором он призывал поддержать Советскую Армению и улучшить ее экономическое положение. Сегодня, когда армянский народ переживает трудные времена: мы потеряли Арцах, наша государственность находится под угрозой, более уместно обратиться к нашему патриотическому духовному деятелю и поднять дух народа через его образ с намерением вселить надежду на будущее.
Keywords: Հաղորդումներ; Հայ եկեղեցւոյ գործիչներ